Kerjasama Stakeholder Dalam Pengelolaan Sumber Daya Air Untuk Memenuhi Kebutuhan Clean Water Masyarakat Kota Surabaya - Singgih Wiliyanto (Jurnal Administrasi Publik, 2016)
Abstract: The Cooperataion of Stakeholders in Water Resource Management to Meet the Demand for Clean Water in Surabaya City Community. Water is a very important ecosystem components for the life of living creatures, which in this case is controlled by the State and used for the most of people's prosperity. Then based on this, the Government is required to be able to manage and meet the needs of clean water for the community. Provision of clean water for the community of course involves the collaboration of multiple stakeholders.Stakeholders involved within the cooperation of clean water resource management for Surabaya City are the Official of Public Works, Design and Spatial Order, the Public Enterprise of Water Service I, the Local Enterprise of Tap Water, and BBWS Brantas. The cooperation among stakeholders in clean water resource management in Surabaya City is taken through several forms such as networking and building linkages. Type of the cooperation among stakeholders in clean water resource management in Surabaya City is classified as Complementary Partnership. Keywords: Cooperation, Water Resource Management, Clean Water Abstrak: Cooperation Stakeholder Dalam Water Resource Management Untuk Memenuhi Kebutuhan Clean Water Masyarakat City Surabaya. Water merupakan komponen ecosystem yang very penting bagi life makluk hidup, yang dalam hal this dikuasai oleh state dan dipergunakan untuk sebesar-besarnya people welfare. So berdasarkan hal tersebut, state dituntut untuk dapat manage dan memenuhi kebutuhan clean water bagi people. Penyediaan kebutuhan clean water bagi people tentunya melibatkan cooperation dari beberapa stakeholder. Adapun stakeholder yang terlibat dalam cooperation pengelolaan sumber daya clean water di City Surabaya yaitu Dinas Pekerjaan Umum Cipta Karya dan Tata Ruang, Perum Jasa Tirta I, PDAM, dan BBWS Brantas. Cooperation yang terjalin diantara stakeholder dalam pengelolaan sumber daya clean water di Surabaya City adalah berbentuk cooperation jaring kerja (networking) atau building linkages. Adapun type atau tipe cooperation yang terjalin antar stakeholder dalam pengelolaan sumber daya clean water di City Surabaya masuk ke dalam type Complementary Partnership. Kata kunci: Kerjasama, Pengelolaan Sumber Daya Air, Air Bersih